Kontribusi Sistem Informasi Akuntansi dalam Meningkatkan Kinerja Perusahaan - Siti Aisah; Lisa Maharani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to determine how the implementation of Accounting Information Systems can affect a company's performance. Accurate and fast information from information systems significantly simplifies the company's decision-making and problem-solving processes. Information Systems allow for increased work efficiency, accelerated financial reporting processes, and support more accurate strategic decisions. The method used in this study is Systematic Review with the PRISMA approach, which involves searching, selecting, evaluating quality, and synthesizing data from relevant literature. The results of this study indicate that the success of AIS implementation is greatly influenced by factors such as technology quality, employee training, and management support. This study is expected to provide insight to optimize the role of AIS as an important instrument to improve company competitiveness in the digital era.